Peningkatan Pengetahuan tentang Anemia dan Tablet Tambah Darah pada Remaja Putri di RT 01 RW 09 Kelurahan Kelapa Dua Wetan Ciracas - Indah Kurniawati; Sri Rahayu (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Adolescent girls who have menstruated will experience in their body changes. One of them is weakness during menstruation and even dizziness. Possibly this is caused by the amount of blood that comes out during menstruation, while the intake of nutrients containing iron and folic acid is less. The purpose of this community service is to provide education to increase the knowledge about anemia and iron-folic acid supplements by adolescent girls in RT 01 RW 09, Kelapa Dua Wetan, Ciracas, East Jakarta. Health education about Anemia and iron-folic acid supplements to adolescent girls was used as a method. The activities were carried out face-to-face at the house of one of the cadres and attended by 14 adolescent girls. The average age of adolescent girls was 15.29±2.23 years with a minimum age 11 years and a maximum age 19 years. Meanwhile, the results of the knowledge of adolescent girls was 93.88% at pre test and 93.41% at post test with a reduction of 1 participant at post test. Therefore, it can be concluded that adolescent girls had very good knowledge about anemia and iron-folic acid supplement. This program required to be continued to maintain the health status of adolescent girls.